Marine water quality of a densely populated Pacific atoll (Tarawa, Kiribati): Cumulative pressures and resulting impacts on ecosystem and human health. (February 2021) - Graves, Carolyn A.; Powell, Andy; Stone, Michelle; Redfern, Farran; Biko, Teema; Devlin, Michelle
Abstract: The resilience of coastal ecosystems and communities to poor environmental and health outcomes is threatened by cumulative anthropogenic pressures. In Kiribati, a developing Pacific Island country where human activities are closely connected with the ocean, both people and environment are particularly vulnerable to coastal pollution. We present a survey of environmental and human health water quality parameters around urban South Tarawa, and an overview of their impacts on the semi-enclosed atoll. Tarawa has significant water quality issues and decisions to guide improvements are hindered by a persistent lack of appropriate and sufficient observations. Our snapshot assessment identifies highest risk locations related to chronic focused and diffuse pollution inputs, and where mixing and dilution with ocean water is restricted. We demonstrate the importance of monitoring in the context of rapidly changing pressures. Our recommendations are relevant to other atoll ecosystems where land-based activities and ocean health are tightly interlinked. Highlights: Eutrophication in Tarawa Lagoon is leading to localised oxygen depletion. Human waste inputs into heavily used coastal waters pose a risk to public health. Insufficient observations of evolving pressures limit process-level understanding.